2016
DOI: 10.3390/ma9110910
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet Printing of Functional Materials for Optical and Photonic Applications

Abstract: Inkjet printing, traditionally used in graphics, has been widely investigated as a valuable tool in the preparation of functional surfaces and devices. This review focuses on the use of inkjet printing technology for the manufacturing of different optical elements and photonic devices. The presented overview mainly surveys work done in the fabrication of micro-optical components such as microlenses, waveguides and integrated lasers; the manufacturing of large area light emitting diodes displays, liquid crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(98 citation statements)
references
References 265 publications
(334 reference statements)
2
86
0
Order By: Relevance
“…Printing methods have traditionally been utilised to mass produce items and images-at a low cost and with a large throughput. Both traditional and modern processes, including screen, gravure and inkjet printing, have been exploited and re-purposed across a broad number of fields, such as the production of flexible electronics [1], biosensors [2] and optical lenses [3]. Therefore, research into alternative print processes can be seen, not only as a route for obtaining a high-quality reproduction of an image, but also as a broader fabrication technique.…”
Section: Introductionmentioning
confidence: 99%
“…Printing methods have traditionally been utilised to mass produce items and images-at a low cost and with a large throughput. Both traditional and modern processes, including screen, gravure and inkjet printing, have been exploited and re-purposed across a broad number of fields, such as the production of flexible electronics [1], biosensors [2] and optical lenses [3]. Therefore, research into alternative print processes can be seen, not only as a route for obtaining a high-quality reproduction of an image, but also as a broader fabrication technique.…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing techniques, such as two‐photon lithography and 3D printing, are becoming more and more relevant in biotechnology, giving the possibility to produce complex 3D structures on different length‐scales and becoming amenable to many different materials . It has been shown that LC materials can be utilized with these techniques with the characteristic molecular order remaining preserved during the photo‐crosslinking process, or even induced and patterned due to shear forces in the 3D printing process . Van Oosten et al achieved the construction of bioinspired artificial cilia for mixing applications and microfluidic pumping (Figure d) .…”
Section: Polymeric Photoactuators: Moving Toward Artificial Musclesmentioning
confidence: 99%
“…Even though the lifetime of organic dyes under strong optical excitation is limited due to photobleaching [18][19][20], their use in low cost sensing applications and single-use devices might be favorable compared to more expensive semiconductor devices. The possibility to locally deposit the dye-doped polymer material on the substrate via ink-jet printing can decrease fabrication costs even further and adds additional design flexibility [21,22]. Compatibility to CMOS fabrication processes enables the co-integration of organic polymer based technology with microelectronics.…”
Section: Introductionmentioning
confidence: 99%